Derotational Plate Augmentation with Retention of Intramedullary Interlocking Nail in Resistant Nonunion at Distal Femur Shaft - Muhammad Khalid Syed, Waqas Ahmad, Syed Imran Haider, Muhammad Mazharrafique, Zafar Ali, Muhammad Iqbal, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Non-union in femur shaft after satisfactory treatment with closed intramedullary interlocking nail is not very common. This nonunion is always a challenging condition for surgeon. These nonunion are usually treated by dynamization, close exchange nail with larger diameter, retention of nail and onlay bone graft, removal of nail and fixed with plates and bone graft, removal of nail and application of cast brace and sometimes removal of nail and applications of external fixators. But no treatment is’ gold standard’ the rotational instability is blamed to be one of the most common reason of nonunion. Aim: To control rotational instability, we did plate augmentation with or without bone grafts without removing the nail to treat this nonunion. Methods: Total patients were 16. Proximal and distal interlocking screws were removed, nonunion site was opened, compression at nonunion site was done, and broad DCP was applied as de rotation plate with or without bone grating. We excluded fracture less than one-year duration and fracture with infective nonunion. Results: In 12 patients bone grafting was done where there was less callus or there was suspicion of atrophic non-union. We got union in all patients. 6.25 months were average time of union. 13 months was average time between the primary and secondary surgery. 71 minutes was means surgical time. Complications or implant failure were not noted. 0.9 cm was average residual limb shortening and 115 degrees was average range of motion at knee joint. Conclusion: Nonunion in distal femur shaft fracture with interlocking nail in situ is reliable and effective procedure Keywords: Distal femur, plate, External fixator. Bone grafting